Neuropathic arthropathy of the shoulder associated with chronic inflammatory demyelinating polyneuropathy: A case report: Neuropathic arthropathy associated with demyelinating polyneuropathy - Ortanca, Burcu; Armağan, Onur; Bilici, Mazlum Doğan (Journal of Surgery and Medicine, 2023)
Neuropathic arthropathy is a chronic degenerative arthropathy that results from a neurosensory deficit of the affected joint. According to neurovascular theory, the loss of sensation of the joint is responsible for its formation. Chronic inflammatory demyelination polyneuropathy (CIDP) is a rare disease with sensorimotor involvement in which demyelination and axonal damage occur in the peripheral nerves as a result of an abnormal immune response. A case is presented of a 64-year-old male patient with a diagnosis of CIDP who had Charcot arthropathy of the right shoulder.